CT-FFR: Clinical Application - Sidhi Laksono Purwowiyoto (The Indonesian Heart Association, 2018)
Invasive fractional flow reserve (FFR) is the gold standard for guiding decision making to identify patients who would benefit from revascularization. Now, computed tomography can also do that by using computational fluid dynamics to calculate fractional flow reserve values from coronary CT angiography image data sets, known as CT-FFR. CT-FFR as an alternative method beside invasive FFR enables the identification of lesion-specific in coronary tree noninvasively. CT-FFR has showed significant improvement in specificity and positive predictive value and decreasing the frequency of using invasive coronary angiography. Abstrak Pemeriksaan invasif fractional flow reserve (FFR) adalah standar emas untuk memandu pengambilan keputusan dalam mengidentifikasi pasien apakah yang mendapat manfaat dari revaskularisasi. Sekarang, computed tomography juga dapat melakukannya dengan menggunakan dinamika cairan terkomputasi untuk menghitung fractional flow reserve dari kumpulan data gambar angiografi koroner CT, yang dikenal sebagai CT-FFR. CT-FFR sebagai metode alternatif selain FFR invasif memungkinkan identifikasi spesifik lesi pada koroner secara non-invasif. CT-FFR telah menunjukkan peningkatan yang signifikan pada spesifisitas dan nilai prediksi positif dan penurunan frekuensi penggunaan angiografi koroner invasif.